Komunikasi Pemasaran Perspektif Islam - Effendy, Erwan; Bil’ibad, Rahman Asro; Panjaitan, Abiyyu Zhafran Khairy (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
This study aims to find out how to market products or services in an islamis way or also called sharia marketing. This study used a qualitative method, namely a method with data collection techniques through direct observation. The subjects of this study were traders in the MMTC market in the Pancing area. Data collection techniques in this study are observation and document study. Observation is the process of directly observing human behavior in their daily activities, while document study is a method of collecting data by examining various documents for analysis. The result of the study show that there are some traders who are honest with consumers about their trade, such as telling consumers about the advantages and disadvantages of the products being sold, and there are also those who do not tell the shortcomings of their products. There are those who smile kindly at their prospective customers, there are also those who give a look of displeasure and many more which will be discussed further in the results and discussion. Keyword: Communication, Marketing, Islam